PREDIKSI BESAR EROSI DENGAN METODE USLE DI KECAMATAN CANDUANG KABUPATEN AGAM - ahmad Fadhil; Ratna Wilis (DEPARTEMEN GEOGRAFI FIS UNP, 2019)
ABSTRACT This research aims to discuss Predicion of Erotion in Caduang Subdistrict, Agam Regency. The Method used is descriptive method with quantitaive approach. The variables in this study predict the erotion that occurs on agricultural land cover with the determination or planting technique that is not in accordance with conservation. Determination of sample points in was carried out of using the porposive sampling method. Data collection technique used were primary and secondary data from BMKG, BPDAS-HL Agam Kuantan, BNPB, BAPEDA and Canduang Subdistrict goverment. Data analysis technique carried out by means of observation with data analysis technique in this research are field analysis. The result of research : prediction of erotion in Canduang Subdistrict classed by light, medium and heavy which erosion risk class I, II and III. Keyword : Erotion, USLE, Prediction ABSTRACT This research aims to discuss Predicion of Erotion in Caduang Subdistrict, Agam Regency. The Method used is descriptive method with quantitaive approach. The variables in this study predict the erotion that occurs on agricultural land cover with the determination or planting technique that is not in accordance with conservation. Determination of sample points in was carried out of using the porposive sampling method. Data collection technique used were primary and secondary data from BMKG, BPDAS-HL Agam Kuantan, BNPB, BAPEDA and Canduang Subdistrict goverment. Data analysis technique carried out by means of observation with data analysis technique in this research are field analysis. The result of research : prediction of erotion in Canduang Subdistrict classed by light, medium and heavy which erosion risk class I, II and III. Keyword : Erotion, USLE, Prediction